Changes in a functional condition of prooxidant system in guinea pigs’ blood in experimental allergic alveolitis and their correction with thiotriazolin - Sadljak, Oksana Volodumurivna; Solvar, Zoryana Ljubomurivna; Baida, Mariana Ljubomurivna (Journal of Education, Health and Sport, 2018)
The study shows that significant elevation of conjugated dienes and malondialdehude in the blood of guinea pigs depend on experimental allergic alveolitis duration was detected. Oxidative stress can arises from overproduction of reactive oxygen species(ROS) by metabolic reactions that use oxygen. ROS also affects the expression of several genes by upregulation of redox-sensitive transcription factors. Regulation of redox state is critical for cell viability, activation, proliferation, and organ function. Corrective effect of thiotriazoline on these indicators have demonstrated .